Current data on Short-toed Eagle in the Nizhny Novgorod Region, Russia - Pavel M. Shukov (Пернатые хищники и их охрана)
The article presents current results of a study of Short-Toed Eagle (Circaetus gallicus) distribution, abundance, and ecology in Nizhny Novgorod region. We designed a network of auto routes to survey the area and subsequently covered it in a four-wheel drive vehicle combined with walking through upland bogs and forest margins by foot. Observations were carried out in 30 districts of the region. Hunting Short-Toed Eagles were observed from natural hills through binoculars. Nests were detected based on adult birds’ observations and analysis of satellite images of the surveyed areas. Photo and video recording of birds and nests was carried out using a SLR camera and a quadcopter. In 2015–2023 observations were carried out on 49 breeding territories.